Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte. Issue 12 (18th May 2021) - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang
Abstract: Anodic zinc oxide (AZO) layers are attracting interdisciplinary research interest. Chemists, physicists and materials scientists are increasingly devoting attention to fundamental and application‐related research on these layers. Research work focuses on the application as semiconductor, corrosion protector, adhesion promoter, abrasion protector, or antibacterial surfaces. The structure and crystallinity essentially determine the properties of the AZO coatings. The type and concentration of the electrolyte, the applied current density or voltage as well as the duration time enable layer structures of structural variety. The article gives an overview of the different possibilities of anodic treatment, whereby the voltage and the current type are the main distinguishing criteria. Presented is the electrolytic oxidation (anodizing) and the electrolytic plasma oxidation (EPO). The electrolytic etching is also a process of anodic treatment. However, it does not produce AZO layers, but rather a degradation of the zinc layer. The review article shows the parameters used so far (electrolyte, current type, current density, voltage) and points out the influence on the formation of AZO structures in dependency to the used electrolyte. Abstract : Think anodic : This review provides an overview of the different possibilities of anodic treatments of zinc oxide, in which the voltage and current type are the main distinguishing criteria. We summarize the parameters used so far (electrolyte, current type, current density, voltage) and highlight the influence on the formation of anodic zinc oxide (AZO) structures in dependency to the used electrolyte.